THE MAJOR TRENDS IN THE PENAL SYSTEM - Ivan Valentinovich Evseev (Science and Innovation Center Publishing House, 2016)
The paper considers the development of scientific knowledge concerning the system of imprisonment as a criminal penalty. The author defines his own vision of the issue of what constitutes the penal and penitentiary system. The following categories are explained from the point of view of the encyclopedic knowledge, namely: prison studies, criminology, penology, etc. For each of the listed categories the author determines its place in the legal knowledge system.